Accuracy in the inference of nursing diagnoses: a scoping review protocol (Research, Society and Development, 2021)
Objective: to describe the methodological steps of a review protocol, to map the scientific knowledge of accuracy of nursing diagnoses. Methodology: This scoping review will be developed as proposed by Arksey and O'Malley and adopted by The Joanna Briggs Institute Reviewers' Manual. For the writing of the study, the PRISMA Extension for Scoping Reviews will be used. An open search will be carried out in the databases, in addition to a search in gray literature, without limitation regarding the year of publication, language and type of design. Additionally, a search for articles will be carried out by reading the references of the studies included in the review. They will include primary and secondary studies that address diagnostic accuracy. Documents such as letters, comments, editors and opinion articles will be excluded. The selection of studies by reading the titles, abstracts and full text will be conducted by two independent reviewers. Data extraction takes place through a form built by the authors. Data will be organized, summarized and propagated in terms of extent, nature, distribution and recurring patterns, and the results will be communicated narratively and through figures and network maps. Conclusion: It is expected that the construction of this protocol will enable the development of a research with the least amount of biases possible, as it will make clear the methodological steps for the progress of a scope review about the accuracy in inferring nursing diagnoses.